2019
DOI: 10.46743/2160-3715/2019.3972
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Co-Teaching for Emergent Arabic-English Literacy

Abstract: In this paper we explore teachers’ experiences of co-teaching within a new bilingual (Arabic/ English) model in public Kindergarten schools in the United Arab Emirates. The main objective was to understand teachers’ experiences with intercultural teaching for biliteracy in this context. We interviewed six pairs of co-teachers. These co-teachers represent six of the nationalities of teachers working in public Kindergartens in Abu Dhabi, thereby representing a cross-section of the cultural context of teaching in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Research on translanguaging is scarce in the Arab world, particularly in higher education. Dillon [31] looked at experiences of co-teaching within a new bilingual (Arabic/English) model in public kindergartens in the United Arab Emirates and noted that few studies had looked at Arabic-English biliteracy [32,33]. Dillon and Gallagher [31] interviewed six pairs of kindergarten co-teachers in Abu Dhabi.…”
Section: Translanguaging In the Arab Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on translanguaging is scarce in the Arab world, particularly in higher education. Dillon [31] looked at experiences of co-teaching within a new bilingual (Arabic/English) model in public kindergartens in the United Arab Emirates and noted that few studies had looked at Arabic-English biliteracy [32,33]. Dillon and Gallagher [31] interviewed six pairs of kindergarten co-teachers in Abu Dhabi.…”
Section: Translanguaging In the Arab Worldmentioning
confidence: 99%
“…Dillon [31] looked at experiences of co-teaching within a new bilingual (Arabic/English) model in public kindergartens in the United Arab Emirates and noted that few studies had looked at Arabic-English biliteracy [32,33]. Dillon and Gallagher [31] interviewed six pairs of kindergarten co-teachers in Abu Dhabi. They found that different classroom practices, such as translanguaging and class management, were enhanced by co-teaching, while flexible translanguaging, in turn, supported co-teaching and biliteracy outcomes.…”
Section: Translanguaging In the Arab Worldmentioning
confidence: 99%
“…Em todas as formas de se estruturar a etapa de formulação de políticas públicas, sempre haverá a exigência das ações por parte de algum agente, sendo ele os Governos ou dos agentes externos, ou entidades do terceiro setor envolvidos (BAPTISTA, 2019;DILLON;GALLAGHER, 2019;PERONI;SUSIN;MONTANO, 2021). O planejamento também precisa considerar a garantia dos objetivos, prioridades e atividades para formulação da política pública (DOUGLAS et al, 2016;FRANCO, 2022).…”
Section: Planejamentounclassified
“…O gestor e sua equipe devem estar preparados para elaborar a política pública com compromisso, competência teórica, técnica e política. Os agentes da equipe formuladora precisam compreender a realidade da sociedade em sua complexidade, levando em consideração as partes que influenciam no processo de decisão e análise da política pública local (BESIC et al, 2017;BULLOUGH, 2015;DILLON;GALLAGHER, 2019;MACHIDA;WALSH, 2015;MARINZECK-SANTOS, 2021;SANT'ANNA, 2020;STROGILOS;TRAGOULIA, 2013).…”
Section: Formação De Equipeunclassified
See 1 more Smart Citation